The Historical Development of Primary and Islamic Education in Indonesia: From Empire to Reform Era - Muh Syauqi Malik; Kartika Dwi Astuti; Vit Ardhyantama; Muhammad Imaduddin; Hana Andriningrum; Helda Kusuma Wardani (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
The phrase "Never Leave History" (Jasmerah) from Soekarno emphasized the importance of historical awareness. This article examines the evolution of basic education and basic Islamic education in Indonesia from the Islamic kingdom to the Reform era with a qualitative approach based on a literature review. Key findings reveal a significant shift in the Islamic basic education curriculum, transforming from a traditional Islamic boarding school-based approach to a formal school model that integrates modern science and technology. In addition, a dynamic pattern of education policy was found, seeking to balance the preservation of local-religious values with the demands of modernization and national development. This study also confirms that Islamic education functions not only as a transmission of knowledge but as a process of forming character, social identity, and cultural resilience according to Islamic teachings. The implications of this research are very important for the development of education policies that are inclusive, holistic, and responsive to social and cultural change. The unique contribution of this research can be seen from the cross-era analysis that provides a comprehensive picture of the resilience and adaptability of Islamic education in the face of socio-political challenges, while strengthening the historical foundations and Islamic values in the national education system.